Teori-Teori Belajar dan Aplikasinya dalam Pembelajaran - Fithriyah, Dewi Niswatul (STIT Al-Ibrohimy Bangkalan, 2024)
Learning theory is a step that can help teachers or educators to educate and convey knowledge to students or learners. Basically, there are many learning theories, but there are four that are often used by some teachers, namely behavioristic learning theory, cognitive learning theory, constructivist learning theory, and humanistic learning theory. Of these theories, each has different applications and different figures. The main goal of learning theory is to support the development of effective and efficient learning. By understanding learning theory, you can create effective and efficient learning activities. The method used in this research is the library method, which is based on books, research results, journals and articles related to learning theory and its applications. This research aims to describe various learning theories and their application in learning activities.